Fungal volatile organic compounds show promise as potent molluscicides. Issue 12 (1st October 2019) - Khoja, Salim; Eltayef, Khalifa M; Baxter, Ian; Bull, James C; Loveridge, Edric Joel; Butt, Tariq
Abstract: BACKGROUND: Slugs and snails constitute major crop pests. Withdrawal of metaldehyde has prompted a search for more environmentally friendly yet fast acting molluscicides. This study investigated the response of representative molluscs to conidia and volatile organic compounds (VOCs) of the insect pathogenic fungus Metarhizium brunneum Petch. RESULTS: Conidia of M. brunneum had antifeedant/repellent properties with repellency being dependent upon the fungal strain and conidia concentration. Three commonly produced fungal VOCs, 1‐octene, 3‐octanone and 1‐octen‐3‐ol, were repellent at low doses (1–5 μL) but could kill slugs and snails on contact or fumigation. At the highest dose tested (10 μL), 100% mortality was achieved for Cornu aspersum Muller (garden snail) and Derocerus reticulatum Muller (grey field slug) within 1 h post‐treatment with the first deaths being recorded in <11 min. Aqueous formulations (20% v/v) of the most potent VOCs, 3‐octanone and 1‐octen‐3‐ol, could be sprayed onto plants to kill or drive the pest of the crop with no phytotoxic effects. CONCLUSION: The sensitivity of terrestrial molluscs to 3‐octanone and 1‐octen‐3‐ol and the ephemeral nature of these compounds makes these excellent candidates for development as mollusc repellents or molluscicides. © 2019 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Slugs and snails avoid plants treated with conidia and VOCs of the insect pathogenic fungus Metarhizium brunneum . The VOCs show promise as mollusc repellents or molluscicides.